Enhanced antireflection and absorption in thin film GaAs solar cells using dielectric composite nanostructures - Yanyan Wang; Jiali Chen; Ruiying Zhang; Min Qian (Heliyon)
This study investigates the application of dielectric composite nanostructures (DCNs) to enhance both antireflection and absorption properties in thin film GaAs solar cells, which are crucial for reducing production costs and improving energy conversion efficiency in photovoltaic devices. Building upon previous experimental validations, this work systematically explores the underlying theoretical mechanisms using the finite difference time domain (FDTD) method to analyze the light interaction with the proposed DCNs. The results show that the combination of Mie resonance, Fabry–Perot resonance, and guided resonance, induced by the surface structuring of the DCNs, significantly enhances light absorption in the active layer, particularly at longer wavelengths. For solar cells featuring a 500-nm-thick absorber layer, SARL-decorated solar cells demonstrated an average reflectivity of 12.18 %, whereas those incorporating DCNs exhibited a significantly reduced average reflectivity of 4.52 %. These findings indicate that DCNs structures are highly effective in enhancing the performance of thin and ultra-thin GaAs solar cells by minimizing surface reflection and increasing photon utilization, offering a promising solution for high efficiency, cost effective photovoltaic devices.